Rehabilitating and closing a coal tailings storage facility in Central Queensland, Australia: a non-conventional approach based on ecological engineering of pedological processes - Roddy, B.; Huang, L.; Lockhart, C. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Among the mining disturbance domains, tailings storage facilities (TSFs) often present the most challenging to rehabilitate, as conventional engineering approaches necessitate dewatering, capillary breaks, thick capping materials, and topsoil covers, frequently incurring costs in the hundred millions to rehabilitate. This study examines a ~200 ha coal TSF that is no longer operational. Field observation revealed that while the surface is predominantly bare, one specific area of the TSF was covered with 0.5 m of coal rejects (~15 years old). This area exhibited establishment of self-seeded grasses, shrubs, and eucalypt trees. In collaboration with the University of Queensland, a preliminary study was conducted to investigate the physical and chemical properties that have promoted soil development to support the observed plant growth. Samples from the non-vegetated tailings were compared with those from the coal reject growth area. The coal tailings are alkaline (pH 8.6–9.0), saline (1,300–5,300 µS/cm), dispersive (exchangeable sodium percent of 20–37), low in nutrients and cation exchange capacity (CEC), and nearly impermeable (hydraulic conductivity of 10-4m/day). In contrast, the coal reject cover had a sandy/stony particle size distribution (PSD), neutral pH, low salinity, low nutrient/CEC, and was non-dispersive. A pot trial demonstrated that Rhodes grass, watered only and without fertiliser or amendments, successfully grew over 14 months in the mixture of 40% rejects, 40% waste rock, 10% tailings, and 10% hay mulch. The findings support the viability of an ecological engineering approach that utilises site waste materials (rejects and waste rock) to stimulate pedological processes and create a new growth media in situ. This approach mimics a natural duplex soil system found in sodic landscapes of Central Queensland, which can support native vegetation with low phosphorus and nitrogen requirements in low-rainfall areas. By employing this method, it may be possible to significantly reduce costs typically associated with conventional engineering solutions, decrease the reliance on topsoil (which in often scarce), and effectively use site waste materials, all while achieving rehabilitation objectives.